According to the fire, my house burned down: An Investigation into Thai Student Use of the English Phrase “according to”. - Humphries, Scott (Journal of Studies in the English Language, 2014)
Observation has shown that some Thai university students in English intermediate writing courses have used constructions of the phrase “according to” that, while similar to each other, differed from the accepted normal construction in English. In an attempt to discover the origins of student use, document and empirical research methods were set up and applied. Initial document research was performed in which the phrase was checked in several English grammar guides readily available in Thailand to see if the explanation of the phase could be interpreted by Thai learners in a way which would lead them to use the phrase to show causality, which some of them had done, e.g. “according to a fire at my head office, a lot of my computer data were destroyed”. These books were then further examined to determine if they gave any indication that another student construction, namely “according to psychotherapist Paula Hall explains”, is possible in English. During the empirical research phase, the students who had either used “according to” correctly or incorrectly in their writing were individually interviewed as to their acquisition of the phrase. These interviews were recorded and later transcribed as verbal data for use as a basis as to the origin of student use. The students were also asked to fill out a short questionnaire which asked about their personal background, as well as their earlier background in English language acquisition and study. Using the domain of error analysis as a theoretical framework, this paper discusses and examines the results of the research. It attempts to draw conclusions, first, about whether the student usage is incorrect and, second, if the phrase was used in error, whether the error was due to the way the construction was learned or whether it was the result of some other factor, such as first language interference.